In vitro antiviral activity of plant extracts from Clinacanthus nutans - Noor Zarina, Abd Wahab; Aziah, Azizul; Norhazilah, Muhamad; Nazlina, Ibrahim (2021)
Clinacanthus nutans is generally used to treat many diseases in folklore remedies. Whole dried plants were macerated with methanol for crude extract preparation. The aim of this study was to evaluate the cytotoxicity and antiviral activities of C. nutans crude extract. Cytotoxicity screening against Vero cells using MTT assay showed that the CC50 values for crude extract of C. nutans was 1.625 mg/mL. These results demonstrate that the extract prepared from C. nutans was non-cytotoxic to the cell with potential antiviral activity. Plaque reduction assays were carried out to evaluate the antiviral activity of C. nutans extract against herpes simplex virus type 1 (HSV-1). These include post-treatment, pre-treatment and virucidal assays. The selective indices (SI = CC50 / EC50) of C. nutans extract in post-treatment, pre-treatment and virucidal assays were 11, 6 and 3 respectively. In conclusion, this study showed that C. nutans extract has promising potential to be explored as anti-HSV-1 agent regardless of the mode of treatment.